2016
DOI: 10.4103/2153-3539.177687
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of the diagnostic utility of digital pathology systems for telemicrobiology

Abstract: Introduction:Telemicrobiology is a growing component of clinical microbiology informatics. However, few studies have been performed to assess the diagnostic utility of telemicroscopy systems in evaluating infectious agents.Objective:Evaluate multiple contemporary digital pathology platforms for use in diagnostic telemicrobiology.Materials and Methods:A mix of thirty cases that included viral, bacterial, fungal, and parasitological findings were evaluated by four experts using ×40 whole slide imaging (WSI) scan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
4
4

Relationship

1
7

Authors

Journals

citations
Cited by 12 publications
(3 citation statements)
references
References 9 publications
0
3
0
Order By: Relevance
“…Including microorganisms within the gallery of diagnostic images therefore allows the additive capability to screen for specific organisms. Further, unlike prior digital pathology systems that have had major limitations with the diagnosis of microorganisms,[ 20 ] images acquired with the Hologic scanner were of satisfactory quality to permit the identification of several organisms.…”
Section: Onclusionsmentioning
confidence: 99%
“…Including microorganisms within the gallery of diagnostic images therefore allows the additive capability to screen for specific organisms. Further, unlike prior digital pathology systems that have had major limitations with the diagnosis of microorganisms,[ 20 ] images acquired with the Hologic scanner were of satisfactory quality to permit the identification of several organisms.…”
Section: Onclusionsmentioning
confidence: 99%
“…Similarly, confirmation of microorganisms digitally requires higher resolution digital images or scanning at multiple z-levels. [ 47 ]…”
Section: Discussionmentioning
confidence: 99%
“…Multiple studies in our laboratory and others have shown that similar diagnoses can be obtained using digital and light microscopy and that digital microscopy can be effectively used for primary surgical pathology diagnosis, telepathology, teaching, and other applications. [222324252627282930] Digital pathology systems offer a variety of logistical advantages, as they can streamline the flow and storage of cases, help reduce clerical errors, shorten turnaround time, and provide other operational efficiencies. These have stimulated an increasing interest in using them to replace the time-tested method of distributing glass slides throughout a laboratory for examination with light microscopes.…”
Section: Discussionmentioning
confidence: 99%